Inclusão escolar e o portador de deficiência nas aulas de Educação Física das redes municipal e estadual de Uberlândia - Sousa, Sônia Bertoni (2002)
This study had as central thematic the deficiency bearer-DB inclusion in the regular school and, more specifically, in the Physical Education classes. The general objectíve was to verify how is the situation lived by the deficiency bearer in Physical Education classes in Fundamental Teaching, of municipal and state public net, in Uberlândia-MG city. It is a field research with criticai analytic character. They were applied two questionnaires containing open, closed and mixed subjects: one for Physical Education teachers in Fundamental Teaching, of municipal and state public net, in Uberlândia-MG city, and other questionnaire destined to the principais of those schools. Therefore, 102 schools of the fundamental teaching composed the population of this study: 40 municipal net schools and 62 state net. The questionnaires were applied to all Physical Education teachers and all the principais of the supra-mentioned schools, with a total of 102 principais and 264 Physical Education teachers. The results indicated that: there are countless difficulties to be faced by the principais, teachers and DB of nets municipal and state schools Uberlândia-MG city; the materiais, the physical space, the contents organization and the professionals' formation are not suitable with students PD'S needs. The reality in both municipal net and state net is precarious, critic, lacking and it demands attention, cares and investments. We ended that the perspective that comes for the deficiency bearers in the Physical Education classes in Uberlândia city, is distant of reaching the politics of school inclusion. It is possible to affirm that even the integration politics was not in fact reached yet. Because there are not the basic conditions of access and studenfs DB permanence in them school guaranteed, more specifically in the Physical Education classes. It is evident when we observed that the number of deficient reduces sensibly in the most advanced series.